Impact of Organizational Communication on Employee Relations with Trust as a Mediating Variable - Melianto, Donny; Kurnadi, Kurnadi; Ulumuddin, Ulumuddin (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study investigates the relationship between organizational communication, employee relations, and organizational trust in a multinational company setting, focusing on PT. Sumiden Serasi Wire Products. Grounded in Social Exchange Theory (SET), this research explores how organizational communication fosters trust, which in turn strengthens employee relations. A quantitative approach was employed, utilizing Structural Equation Modeling Partial Least Squares (SEM-PLS) with SmartPLS 4.0 to analyze data collected from 110 employees, based on Hair et al.'s (2019) indicator-based sampling formula. The findings indicate that organizational communication positively influences employee relations, with organizational trust playing a significant mediating role. Employees who perceive transparent communication are more likely to develop trust, leading to increased job satisfaction, lower turnover intention, and stronger organizational commitment. The study highlights the critical role of trust in mediating the impact of communication on employee relations, providing valuable insights for multinational companies managing diverse workforces. These results underscore the importance of effective communication strategies in enhancing trust and employee engagement, contributing to organizational success and sustainability in a global business environment.